A novel one target game model in the life insurance market. Issue 3 (3rd July 2021) - Hamidoğlu, Ali
ABSTRACT: One target game models are played by two or more players where one player becomes a target of the others in a competitive playing ground. The present paper proposes a novel one target game model in the context of two-player games and provides strategies to control the life insurance market between two companies to decide which one is better for their customers. In this regard, a new perspective is established for building control-based environments to several insurance models controlled by finite sets. Here, different chasing strategies are designed in the insurance market in such a way that one company offers its own current policy for its clients, whereas the other tries to reach the policy of its opponent as close as possible to dominate the current market. The main contribution of this work is to design a better life insurance model for the company by using a game theoretical point of view to develop its current marketing policy. For having a clear vision over the construction, numerical examples are provided to justify the main results of the paper. According to the literature, this work is the first attempt to create a discrete one target game model controlled by a finite set in the life insurance market.